PARMAKLARDA EKSTANSOR GÜÇ KAYBI İLE KLİNİĞE YANSIYAN BİR NEMALİN MİYOPATİ OLGUSU - ŞAHİN, Şevki; AKALIN, Mehmet; KIZILTAN, Meral (Cerrahpaşa Medical Journal, 2014)
Background.- Wide spectrum of genetic defects may lead to congenital myopathies. Thus, clinical features such as age of onset, distribution of weakness and other associating diseases, may very considerably.Diagnostic difficulties are encountered with adult ondet and atypical patterns myopathy. Observation.- This patient, with dismorphic changes, congenital bilateral drop foot, presenting with subacute onset weakness of finger extensors, were diagnosed as .nemaline myopathy. by way of histopathologic examination. In this case report, a rare form of adult onset nemaline myopathy is discussed.